Application of modified Yoon-Nelson nonlinear equation for modeling antibiotics adsorption onto a composite adsorbent - Chukwunonso O. Aniagor; Matthew C. Menkiti (Results in Surfaces and Interfaces)
This study focuses on the adsorptive removal of metronidazole (MET) antibiotics from wastewater using a cellulose-chitosan composite (Ce–C). The composite was synthesized through an in-situ adsorption mechanism, with glutaraldehyde as a crosslinking agent. The Ce–C composite exhibited a swelling capacity of 3.2 mL/g and a BET surface area of 110.53 m2/g. The batch adsorption isotherms revealed a maximum monolayer adsorption capacity of 14.32 mg/g, with the Langmuir model providing the best fit. Kinetic analysis indicated that the pseudo-first-order model best described the adsorption process. The Ce–C composite also demonstrated biodegradability, with a 79.31% mass loss over 25 days, an indication of the eco-friendliness of the composite. The findings suggest that the Ce–C composite is an effective and eco-friendly adsorbent for MET removal from wastewater.